2023
DOI: 10.3390/tomography9020050
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Radiation Dose of Cerebral Angiography Using Conventional and High kV Techniques: A Retrospective Study on Intracranial Aneurysm Patients and a Phantom Study

Abstract: Evaluation of patient radiation dose after the implementation of a high kV technique during a cerebral angiographic procedure is an important issue. This study aimed to determine and compare the patient radiation dose of intracranial aneurysm patients undergoing cerebral angiography using the conventional and high kV techniques in a retrospective study and a phantom study. A total of 122 cases (61 cases with conventional technique and 61 cases with high kV technique) of intracranial aneurysm patients, who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…An increase in the FOV size may affect the spatial resolution, noise characteristics, low-contrast detectability, and radiation dose to the patients. Although some reports have described the physical evaluation, and radiation dose of C-HR CBCT, cerebral angiography, and computed tomography [20,[22][23][24][25][26][27][28], there are no reports on W-HR CBCT. The purpose of this study was two-fold: to evaluate the image quality and radiation dose of W-HR CBCT, compare it with C-HR CBCT, and determine the optimal image reconstruction for AIS-CBCT.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the FOV size may affect the spatial resolution, noise characteristics, low-contrast detectability, and radiation dose to the patients. Although some reports have described the physical evaluation, and radiation dose of C-HR CBCT, cerebral angiography, and computed tomography [20,[22][23][24][25][26][27][28], there are no reports on W-HR CBCT. The purpose of this study was two-fold: to evaluate the image quality and radiation dose of W-HR CBCT, compare it with C-HR CBCT, and determine the optimal image reconstruction for AIS-CBCT.…”
Section: Introductionmentioning
confidence: 99%
“…Yel et al [ 32 ] investigated the radiation dose and image quality of an extremity CBCT system with 55 imaging protocols and identified an optimized parameter setting that resulted in a dose reduction of 18.9% compared to the manufacturer’s recommended protocol. Kirisattayakul et al [ 33 ] demonstrated that the implementation of a high kV technique may provide an effective reduction in radiation dose. Our findings show the effects of BMI and gender on exposure parameter modulation in head and abdominal CBCT scans.…”
Section: Discussionmentioning
confidence: 99%